The use of DNA to nail male enjoyer of sex: a contemporary analysis from Islamic legal perspective - Haneef, Sayed Sikandar Shah (2014)
The issue of using DNA technology to determine the paternity of a child is a controversial issue in Islamic law. Although vast majority of legal scholars acquiesce its use as a means of connecting unidentifiable children or dead bodies to their legal parents, they oppose its use to nail the male enjoyer of the illicit sex. Consequently, the child born out of wedlock is a liability on the female partner in terms of raising and supporting financially. The classic logic for such a lopsided application of child`s paternity was that in the case of female partner, it is easy to ascertain that such a child is her biological progeny but this cannot be proved in the case of her male partner . Consequently, this kind of approach not only has triggered the culture of baby damping normally by naïve but sexually active female believers but has also financially burdened child welfare organizations, to say the least in terms of larger implications for society. This paper, however, argues that in the age of technology invoking the conventional wisdom of non- traceability of male partner in a sexual act no longer holds true. Accordingly, since in Islam, illicit sex is a heinous crime, biological connection of ill-conceived babies to male partners, among others, goes a long way in saving public money for more worthy and pressing societal causes and in curbing promiscuity among Muslims in a given society.